Deteksi Kesalahan International Standard Book Number (ISBN) Deni Hamdani - - STMIK Mataram, Deni Hamdani (IJNS - Indonesian Journal on Networking and Security, 2018)
Abstract: International Standard Book Number (ISBN) functions to uniquely identify a publication or edition of a publication published by a publisher in a particular format. The license of ISBN to the publisher in Indonesia is given by the National Library of Indonesia. Starting January 1, 2007 ISBN writing changes from 10 digit number to 13 digit number by following the pattern of European Article Number (EAN) which is 13 digits. For example 978-0-07-154353-p, where 978 is a prefix element, 0 is a group element (Register Group Element), 07 is a registrant element, 154353 is a unique code of books published by the publisher (publication element), and p is the test character (check digits). To check the correctness of the ISBN code the formula Σ_ (i_ganjil = 1, i_genap = 3) ^ 12▒ 〖ix_i〗 ≡a (mod 10), with i∈N and p = 10-a are used. Keywords: ISBN Abstrak: International Standard Book Number (ISBN) berfungsi mengidentifikasi secara unik sebuah terbitan atau edisi dari suatu publikasi yang diterbitkan oleh sebuah penerbit dalam format tertentu. Ijin pemberian ISBN kepada penerbit di Indonesia diberikan oleh Perpustakaan Nasional Republik Indonesia. Mulai 1 Januari 2007 penulisan ISBN mengalami perubahan yakni dari 10 digit angka menjadi 13 digit angka dengan mengikuti pola European Article Number (EAN) yakni 13 digit. Misalnya 978-0-07-154353-p, dimana 978 adalah unsur prefiks (prefix element), 0 adalah unsur kelompok (registration Group Element), 07 adalah kode penerbit (registrant element), 154353 adalah kode unik buku yang diterbitkan oleh penerbit tersebut (publication element), dan p adalah karekter uji (check digit). Untuk mengecek kebenaran dari kode ISBN digunakan formula ∑_(i_ganjil=1,i_genap=3)^12▒〖ix_i 〗≡a(mod 10), dengan i∈N dan p=10-a. Kata Kunci: ISBN